"More-than-viral" Eurasian geographies of the covid-19 pandemic: interconnections, inequalities, and geopolitics. Issue 4 (2nd September 2020) - Chan, Kam Wing; Gentile, Michael; Kinossian, Nadir; Oakes, Tim; Young, Craig
ABSTRACT: This paper develops the notion of "more-than-viral" geographies of the covid-19 pandemic. It introduces a set of commentaries on the pandemic in the Eurasian region and its links with the rest of the globe. Taking "more-than-human" perspectives in Human Geography as an inspiration, it develops ways of analyzing the covid-19 pandemic as a "more-than-viral" phenomenon in which human and viral agencies are entangled. In this Introduction to the special issue, we focus on three key intertwined sets of processes that run through this volume, and which both shape, and are being radically reshaped by, the pandemic: interconnections, inequalities, and the geopolitics of disease. Each of these inter-related processes is developed in various ways by the commentaries which make up the special issue.